ANALYZING THE STUDENTS’ABILITY IN READING SHORT STORY BY USING SKIMMING AND SCANNING AT SECOND GRADE OF SMKS KATOLIK KEFAMENANU - Saijao, Maria Fatima; Seran, Yanuarius; Bouk, Edmundus (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2023)
The aims of this research are : to point out whether using reading text is effective to analyzing the students’ ability, to identify to what extend using reading text to analized their English reading short story by using skimming and scanning. The research method that use in this study was descriptive quantitative method. This research used on multiple choice and essay test as the instrument. The participants of the study were 40 students from two classes. The study was conducted for the second grade of SMKS Katolik Kefamenanu. There were 15 items which were used as the instrument. The students were read the question from the text to answer based on their choice. The result of this study showed that there were the data that level of ability are very good from twenty-seven students with their score of grammar aspect 3.20. It is followed by vocabulary that level of ability is good with their score 4.20, and their score on pronunciation aspect was 3.25 so that the level of ability is excellent, on the fluency aspect their score was 4.25 with their level of ability is very good.